2002
DOI: 10.2151/jmsj.80.45
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Anthropogenic Climate Change for Tropical Cyclone Activity: A Case Study with the NCAR CCM2.

Abstract: To investigate the impacts of anthropogenic global warming on tropical cyclone (TC) activity, climate simulations were conducted under the present, and CO 2 -warmed conditions, using the National Center for Atmospheric Research Community Climate Model version 2. The CO 2 -warmed condition includes doubled atmospheric CO 2 concentration, and about 1 C of tropical sea surface temperature (SST) warming. Simulated TCs were objectively selected from twice daily instantaneous outputs during an eight-year time integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
2
38
1
Order By: Relevance
“…Vitart et al (2001) showed strong sensitivity of model TC frequency to changes in convective parameterization, especially to modifications that place restrictions on the production of deep convection (e.g., Tokioka et al 1988), and Vitart et al indicated that parameterization-induced changes in the tropical mean atmosphere may be responsible for the changes in simulated TC climatology. Tsutsui and Kasahara (2000), also obtained results of strong sensitivity to a relative humidity threshold, as a restriction on deep convection. Ueno and Yoshimura (2002) found significant sensitivity of simulated TCs to radiative processes, as well as sensitivity to cumulus parameterization.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Vitart et al (2001) showed strong sensitivity of model TC frequency to changes in convective parameterization, especially to modifications that place restrictions on the production of deep convection (e.g., Tokioka et al 1988), and Vitart et al indicated that parameterization-induced changes in the tropical mean atmosphere may be responsible for the changes in simulated TC climatology. Tsutsui and Kasahara (2000), also obtained results of strong sensitivity to a relative humidity threshold, as a restriction on deep convection. Ueno and Yoshimura (2002) found significant sensitivity of simulated TCs to radiative processes, as well as sensitivity to cumulus parameterization.…”
Section: Introductionmentioning
confidence: 79%
“…There are several studies with this method using relatively-low-resolution global climate models (e.g., Broccoli and Manabe 1990;Haarsma et al 1993;Tsutsui 2002), and a few ones using higher-resolution global models, of about 100-km horizontal grid spacing (e.g., Bengtsson et al 1996;Sugi et al 2002). Bengtsson et al (1996) and Sugi et al (2002) found in their high-resolution-model experiments, that global TC frequency decreases significantly in response to greenhouse warming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on this issue have been undertaken with global climate models (e.g., Broccoli and Manabe 1990;Haarsma et al 1993;Bengtsson et al 1996;Krishnamurti et al 1998;Sugi et al 2002;Tsutsui 2002;Yoshimura et al 2005) and regional nested models (e.g., Knutson et al 1998;Knutson andTuleya 1999, 2004;Walsh and Ryan 2000). Among the problems frequently discussed, the possible changes in the frequency and intensity of future tropical cyclones are more relevant to the present study.…”
Section: Introductionmentioning
confidence: 98%
“…These disasters arouse public interest about the relationship between the number or intensity of tropical cyclones and global warming. A number of studies have been conducted to project future climate associated with warmer sea surface temperature (SST) using increased-CO2 scenarios and a global circulation model (GCM) (Broccoli and Manabe 1990;Haarsma et al 1993;Bengtsson et al 1996;Krishnamurti et al 1998;Royer et al 1998;Shapiro and Goldenberg 1998;Houghton et al 2001;Sugi et al 2002;Tsutsui 2002) and regional nested models (Knutson et al 1998;Knutson and Tuleya 1999;Walsh and Ryan 2000;Knutson and Tuleya 2004). These simulation results, however, are not consistent in the projection of an increase or decrease in the total number of tropical cyclones, although most of the simulations project an increase in the intensity of tropical cyclones.…”
Section: Introductionmentioning
confidence: 99%